(untitled) (Dhaka University Law Journal, 2024)
Although the doctrine of separation of powers has significantly influenced the development of constitutional doctrine in many countries, an acknowledgment of the myriad limitations of the theory allows reevaluating the traditional approach to view institutional governance. This article explores collaborative constitutionalism which sees the state organs not as solitary entities confined to one single function rather as constituent parts of a joint enterprise where each of the organs has its own role to play and they work together. Based on judicial decisions by the courts of Bangladesh, India, and Ireland, three forms of collaboration have been identified where the courts have acted as partners in the joint enterprise of governing with other organs. It has been demonstrated that adopting a collaborative approach allows the courts to perform a proactive and meaningful supervisory role vis-à-vis the other organs of the state to ensure the rule of law. Dhaka University Law Journal, 2023, 34 (2), 115-131